Animality, Moral, and Subjectification: for the otherness recognition beyond the other-human - Rodrigo Avila Colla (Educação (Santa Maria. Online), 2014)
This paper discusses the animality while intrinsic quality of the human. Attempts to their potential as sensitive formative sphere and defends it as a way to create alternative modes of subjectification. Seeks to unveil some natural conditioning inherent to the moral standards. Nietzsche (2005) and Schiller (2002) help to situate the genesis of morality and the human motivations that lead to socialization. Guattari (1992, 2003) contributes to the foundation of an alternative paradigm of subjectification regarding the topic animality. This paradigm seeks to give rise to subjectification ways heterogeneous and open to the absolute otherness, sphere of infinites subjectivizing alternatives. Finally, suggests that the animality be reconsidered as element of exponentiation of the sensitivity in Education.